The potential of endophytic Trichoderma from oil palm (Elaeis guineensis Jacq.) roots of North Sumatra, Indonesia against Ganoderma boninense - Dedek Haryadi; Manjit S Sidhu; Tumpal Panjaitan; Hadi Hendra; Chong, Khim Phin (Malaysian Palm Oil Board, 2019)
Utilisation of endophytic Trichoderma increases tremendously as an alternative control against G. boninense, causal pathogen of basal stem rot (BSR) disease of oil palm. However, investigation of endophytic Trichoderma from Indonesia is still very scarce. The aims of this study were to isolate, identify and investigate the potential of endophytic Trichoderma from oil palm roots. Three potential endophytic Trichoderma species were isolated and further identified using macroscopic, microscopic, and molecular methods. Antagonistic activities of endophytic Trichoderma were tested using dual culture agar and poison food agar assay. A molecular approach using DNA sequencing of 5.8S-ITS region successfully identified the endophytic Trichoderma isolate ET501 as Trichoderma reesei strain RHa, while isolates of endophytic ET523 and ET537 were identified as Trichoderma asperellum isolate F1 and Trichoderma asperellum strain Q1, respectively. Trichoderma reesei ET501 was the most aggressive isolate against G. boninense with PIRG of 95.1% compared to T. asperellum ET523 and T. asperellum ET537 with PIRG of 87.1% and 88.9%, respectively. Meanwhile, T. reesei ET501 showed the strongest antibiosis activity with 100% inhibition in 80% concentration, compared to T. asperellum ET523 and T. asperellum ET537 which gave 12.3% and 90.5% of inhibition, respectively.